A Multi-State Examination of School District Policies to Address Teen Dating Violence - Richey, Ann E. (Journal of interpersonal violence, 2025)
In 2021, 13.6% of United States (U.S.) high school students reported experiencing teen dating violence (TDV). Most states have at least one law for addressing TDV in high schools through policies and/or educational programs. Limited research has been done to analyze the content and variability of school district TDV policies across the U.S., and its association with TDV victimization. Twenty-three large urban school districts across the U.S. were included in the analysis. School district TDV policies were obtained through an online search and were coded for the presence or absence of information pertaining to the scope, prevention education, response to TDV, and implementation of the policy. Self-reported TDV victimization was also obtained for each school district from the 2021 Youth Risk Behavior Survey. Overall, 18 school districts had a written TDV policy available online, with 15 school districts defining TDV in the policy. In terms of prevention education, only two school districts used culturally responsive language for diverse populations in the policy. Although 17 school districts included disciplinary consequences for TDV perpetration in the policy, only 6 school districts specified the consequences. All school districts with a TDV policy designated a liaison for TDV coordination. Overall, the prevalence and odds of self-reported TDV victimization was higher in school districts without a TDV policy compared to school districts with a TDV policy. Although most of the school districts had a TDV policy, there was substantial variation in the content of these TDV policies. Identifying and addressing gaps in school district TDV policies can potentially lead schools to preventing and responding to TDV more comprehensively, ultimately creating safer school environments.